Peningkatan Minat Belajar Melalui Media Powerpoint dan Proprofs Brain Games Bagi Siswa Kelas III - Shofi, A’lauddin (Jurnal Kualita Pendidikan, 2024)
The results of the initial reflection obtained information that the level of student interest in learning at Bermi State Elementary School is still low. To overcome this, the researcher applied Microsoft Powerpoint and Proprofs Brain Games learning media. The method used in this study was Survey Research. The subjects in this study were grade III students of Bermi State Elementary School. The data collection technique used in this classroom action research used questionnaire instruments, tests and documentation. The results of the study showed an increase in student interest in learning after using Microsoft Powerpoint and Proprofs Brain Games media by 56%. Before using the media, out of 25 students, 4 students had good learning interests, 7 had sufficient learning interests, and 14 students had poor learning interests. After using the media, students experienced an increase in learning interests with details of 25 students, 2 students had very good learning interests, 13 students had good learning interests, and 10 students had sufficient learning interests. Thus, it can be concluded that the use of Microsoft Powerpoint and Proprofs Brain Games media can increase the learning interests of grade III students of Bermi State Elementary School, Mijen District, Demak Regency.